2004
DOI: 10.1088/0957-4484/15/10/028
|View full text |Cite
|
Sign up to set email alerts
|

Rapid assembly of carbon nanotubes for nanosensing by dielectrophoretic force

Abstract: The carbon nanotube (CNT) has been widely studied for its electrical, mechanical, and chemical properties since its discovery. However, to manipulate these nanosize tubes, atomic force microscopy (AFM) is typically used to manipulate them one-by-one. This is time-consuming and unrealistic for batch fabrication. In this paper, we will present the manipulation of carbon nanotubes using dielectrophoretic manipulation to rapidly build practical nanosensors. Thus far, we have demonstrated thermal sensors for temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 18 publications
1
57
0
1
Order By: Relevance
“…Tremendous efforts have been made to solve the challenges. Techniques, such as scanning-probe-microscopeassisted patterning, [75][76][77] chemical vapor deposition, [78][79][80] template-directed assembly, [81][82][83] and dielectrophoresis deposition, [84][85][86][87] have been developed trying to achieve controlled integration of CNTs. However, existing drawbacks (such as high processing temperature, slow processing speed, coarse control, liquid phase processing/contamination, low reliability, low yield, and high cost) of individual approaches [75][76][77][78][79][80][81][82][83][84][85][86][87] make it difficult to develop a high- performance-on-demand approach for fabricating CNTbased devices.…”
Section: Controlled Growth and Integration Of One-dimensional Camentioning
confidence: 99%
“…Tremendous efforts have been made to solve the challenges. Techniques, such as scanning-probe-microscopeassisted patterning, [75][76][77] chemical vapor deposition, [78][79][80] template-directed assembly, [81][82][83] and dielectrophoresis deposition, [84][85][86][87] have been developed trying to achieve controlled integration of CNTs. However, existing drawbacks (such as high processing temperature, slow processing speed, coarse control, liquid phase processing/contamination, low reliability, low yield, and high cost) of individual approaches [75][76][77][78][79][80][81][82][83][84][85][86][87] make it difficult to develop a high- performance-on-demand approach for fabricating CNTbased devices.…”
Section: Controlled Growth and Integration Of One-dimensional Camentioning
confidence: 99%
“…Parylene-C (p-xylene) was chosen as the material for the flexible substrate because of its excellent chemical resistance and its ability to coat samples with high levels of uniformity and penetration. Other groups mention coating nanotubes with parylene-c for the purpose of nanotube protection, but have not attempted a transfer onto a parylene substrate [13][14]. We placed the device to be coated inside a PDS 2010 Parylene coater and deposited 19 grams of parylene throughout the chamber, resulting in an actual coating thickness of 25 ” m. Using standard microfabrication techniques, release of the SWCNT-parylene system was accomplished by wet etching the silicon substrate.…”
Section: Device Transfermentioning
confidence: 99%
“…It has been demonstrated that dielectrophoresis (DEP) could provide a way to manipulate the CNTs effectively for separation, orientation, alignment, and positioning, and establish a good electrical connection between CNTs and the external measuring circuit [20][21][22][23]. Unlike the typical method using atomic force microscopy to manipulate CNTs one by one, DEP force can trap and fix bundled CNTs between electrodes in a fast and efficient manner, and make the batch fabrication of nanodevices using nanotubes as components, such as chemical sensor, feasible.…”
Section: Introductionmentioning
confidence: 99%